Occurrence of secondary metabolites in tepals of Asphodelus ramosus - C Chimona; A Karioti; H Skaltsa; S Rhizopoulou (Plant Biosystems, 2014)
Major processes contributing to subtleties of ephemeral flowers of Asphodelus ramosus are related to chemical constituents detected in tepals which expand during cold and wet seasons in the eastern Mediterranean. Luteolin, caffeic acid, chlorogenic, and p-hydroxy-benzoic acids are the main constituents, whereas alkanes, ketones, and fatty acids appear in low amounts.